Accurate detection and quantification of epigenetic and genetic second hits in BRCA1 and BRCA2-associated hereditary breast and ovarian cancer reveals multiple co-acting second hits. (1st July 2018) - Van Heetvelde, Mattias; Van Bockstal, Mieke; Poppe, Bruce; Lambein, Kathleen; Rosseel, Toon; Atanesyan, Lilit; Deforce, Dieter; Van Den Berghe, Ivo; De Leeneer, Kim; Van Dorpe, Jo; Vral, Anne; Claes, Kathleen B.M.
Abstract: Background: This study characterizes thesecond hit spectrum in BRCA1 and BRCA2 -associated breast and ovarian cancers at both gene loci to investigate if second hit mechanisms are mutually exclusive or able to coincide within the same tumor. Methods: Loss of heterozygosity, somatic point mutations and copy number alterations along with promoter methylation were studied in56 breast and 15 ovarian cancers from BRCA1 and BRCA2 germline mutation carriers. A mathematical methodology was introduced to quantify the tumor cell population carrying a second hit. Results: Copy neutral LOH was the most prevalent LOH mechanism in this cohort (BC 69%, OC 67%). However, only 36% of BC and 47% of OC showed LOH in all cancerous cells. Somaticintragenic deletions andmethylated subclones were also found in combination with (partial) loss of heterozygosity. Unequivocal deleterious somatic point mutations were not identified in this cohort. Conclusion: Different mechanisms inactivating the wild type allele arepresent within the same tumor sample at various extents. Results indicate that BRCA1/2 -linked breast and ovarian cancer cells are predominantly characterized by LOH, but harbor a complex combination of second hits at various frequencies. Highlights: Mathematical model to quantify second hits in BRCA1 and BRCA2 -linked breast and ovarian cancer. Second hits coincide with each other in variable amount. BRCA1 and BRCA2 inactivation is subject to both stochastic effects and selection mechanisms. BRCA1 and BRCA2 inactivation by second hits is complex.